Operationalising Article 13 of the Convention on the Rights of Persons with Disabilities the role of assistive technology in ensuring access to justice - McVeigh, Joanne (Frontiers in Rehabilitation Sciences, 2025)
Access to justice is a determinant of the realisation of all other rights, including the right to health, employment, and education. As persons with disabilities experience increased discrimination and social exclusion and are at higher risk of violence than people without disabilities, it is crucial to ensure access to justice in both the civil and criminal legal spheres for people with disabilities. However, persons with disabilities experience multiple barriers at the macro/structural and individual levels to accessing justice. In light of the significance of access to justice for people with disabilities, and the multiple barriers to accessing justice experienced by those with disabilities, this perspective examines the importance of assistive technology in fulfilling the right to access justice. To fulfill the right of access to the justice system, assistive technologies must be more effectively harnessed to provide equitable access to justice for persons with disabilities.